Neutrophil Gelatinase-Associated Lipocalin (NGAL) in Peritoneal Dialytic Effluent: Preliminary Results on the Comparison between Two Different Methods in Patients with and without Peritonitis - Grazia Maria Virzì; Sabrina Milan Manani; Matteo Marcello; Elisa Costa; Davide Marturano; Ilaria Tantillo; Silvia Lerco; Valentina Corradi; Massimo De Cal; Francesca K. Martino; Anna Giuliani; Mariarosa Carta; et al. (Applied Sciences, 2022)
Neutrophil gelatinase-associated lipocalin (NGAL) is a lipocalin involved in the immune response and is significantly high in the peritoneal dialytic effluent (PDE) of peritoneal dialysis (PD) patients with inflammation of the peritoneum membrane (peritonitis). The focus of this study was to match two different techniques for peritoneal NGAL evaluation: NGAL point-of-care test-POCT (NGAL Dipstick—NGALds) versus the laboratory-based NGAL assay and with the white cell count in PDE. In this study, we included 30 PD patients: 17 with peritonitis and 13 without. Peritoneal NGAL was tested by a turbidimetric immunoassay and by NGALds. We noticed a good positive linear correlation between the POCT results and the laboratory-based test and between the peritoneal NGALds and white cell count in PDE (both, p < 0.01). NGALds values resulted in being elevated in patients with peritonitis (300 ng/mL, IQR 300–600) in comparison to patients without (100 ng/mL, IQR 50–150) (p < 0.01). Furthermore, the NGALds test was performed in a median time of 20 mins (IQR 18–21) in comparison with the median time of 65 mins (IQR 55–69) necessary for the laboratory-based test (p < 0.01). The results of the NGALds were coherent with the laboratory-based NGAL and with the white cell count in PDE; furthermore, it was a user-friendly method with real-time findings. NGALds could be an extra tool for the diagnosis of peritonitis, helpful at the bedside of the patient, shortening the length of diagnosis, and if the laboratory-based NGAL test is not accessible.